Teacher Challenges in Preparing Learning Plans in the Independent Curriculum at MI/SD Level - Nadlir, Nadlir; nurulqolbi, Safira; Fardiya, Yuma (Lembaga Riset dan Inovasi Almatani, 2024)
This research aims to identify the challenges faced by teachers in preparing learning plans for the Merdeka Curriculum. The Independent Curriculum which was inaugurated by the Indonesian Ministry of Education and Culture through RI Decree No. 56/M/2022 provides flexibility in learning and requires significant adaptation from teachers. The main problems faced include teachers' lack of understanding of new concepts, difficulties in analyzing learning outcomes (CP), formulating learning objectives (TP), developing learning objective pathways (ATP), and developing teaching modules. The method used in this research is a qualitative approach with a type of library research, relying on data sources from literature such as articles, journals and books. The research results show that teachers still face obstacles in using technology to support learning, difficulties in linking lesson material with other knowledge, designing trigger questions, and providing effective feedback. Apart from that, the lack of clear assessment guidelines in formative and summative assessments is also an obstacle. Other obstacles are limited facilities and infrastructure, as well as the need for teachers to understand and implement differentiated learning. Greater support in the form of training and increased access to technological resources is needed to overcome these challenges. Thus, this research provides important insight into the obstacles faced in implementing the Merdeka Curriculum and steps that can be taken to increase teacher readiness in implementing this curriculum.